Digital differece gap in Spain. impact social and economic (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Information and communication technologies (ICT) and their application in socalled Information Society are presented as a genuine engine of growth and innovation, with no doubt economic, social, cultural and political benefits, for both citizens and enterprises. However, there is a risk that some groups, such as that of women, are set aside of this development of the Information Society, or they don`t have some cases with the same opportunities as men, and there is or expand the digital differece, that is, differences between those who manage to be integrated and can therefore take advantage associated with these technologies and those who are “disconnected” and thus unable to access to its benefits. In this paper we attempt to quantify the gender digital difference in Spain, analyzing their causes, in comparison with neighboring countries and the intervention study aimed at the elimination or reduction.
Keywords: Information and communication technologies (ICT); Information Society; gender digital difference; government intervention.